A tríade de um revés: a crise do governo Dilma sob perspectiva política, econômica e discursiva - Toledo, Matheus Tancredo (2019)
The main theme of this research is the crisis of the government of former president Dilma Rousseff, who began her first term with a relevant popular, parliamentary and business support, and years later went by one of the biggest political and economical crisis of Brazil’s history, which culminated in its overthrow through a parliamentary coup. The main goal is to understand which decisions in an political, economical and discursive approach created weaknesses that made it’s overthrow easier, or hindered it to sustain itself. This government is understood as part of a broader brazilian social phenomenon, the lulismo, understanding its political, social, economic and discursive dimensions. The bibliographic review, which includes the use of secondary data, allowed us to gauge the substantial changes that the Dilma government has adopted in relation to its predecessor, former president Luiz Inácio Lula da Silva. There were crucial breaks in the political conduction of the coalition in the Congress , inside the brazilian political system called “Presidencialismo de Coalizão”, of the economic policy, with a path inflection of the public investment towards a policy based in exemptions, besides the shift towards austerity in the second term, and in the lulista’s discourse, from the populist logical of “riches versus poors” to the post-political discourse of the “Midle Class Brazil”. This paved the way for the government not to have sufficient parliamentary, political and social support to resist the coup offensive of the antilulist bloc that was formed in Dilma’s second term, interrupted in 2016